(untitled) (Research, Society and Development, 2021)
Diabetes is a chronic disease that represents a severe public health problem. The objective was to evaluate aspects related to the prevalence, prevention, care and complications of diabetes in adults in Brazilian federative units(FU). This is an ecological, documentary study, performed with data from the National Health Survey-2013 and 2019, collected from website of the Brazilian Institute of Geography and Statistics. Data analysis was performed to verify the difference in proportions, according to the investigated variables, between 2013 and 2019. There was an increase in the prevalence of diabetes in 26 FU(96.30%), varying 3.3(9.3%); and reduction, in all FU, in the proportion that never evaluated glycemia, varying 3.6(25.9%). The proportion of people who used drugs to control the disease in all FU increased, varying 48.1(93.7%), however, only 5 FU(18.52%) showed an increase in the proportion who obtained medication at "Farmácia Popular" program. The proportion of people who received medical assistance in the last year increased by 22 FU(81.48%), varying 53.2(87.3%), however, in the majority of FU the proportion that performed all complementary exams decreased(n=17) and all consultations with a specialist doctor(n=18). In 14 FU(51.85%) the proportion of hospitalizations increased, varying 4.7(31.4%), while the proportion of people with limitations in usual activities decreased by 18 FU (66.67%) , varying 2.4(20.5%). The prevalence of the disease has increased in the vast majority of FU, highlighting the need for prevention strategies, medical and pharmaceutical assistance, aiming to reduce the problems caused by the disease.